2011
DOI: 10.3892/or.2011.1415
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cδ in tumorigenesis of human malignant fibrous histiocytoma

Abstract: Abstract. Protein kinase Cδ (PKCδ), an isoform of PKC, has been shown to act as a critical mediator of tumor progression and apoptosis; however, its role in musculoskeletal tumors is still unknown. In the current study, we examined the expression of PKCδ in human musculoskeletal tumor tissue samples, and investigated the effects of siRNA downregulation of PKCδ on human malignant fibrous histiocytoma (MFH) cell proliferation, migration, and apoptosis, to elucidate its functional roles in musculoskeletal tumorig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Recently, we reported that Sp1 and PKC regulate the transcriptional expression of TMBIM6 8 . PKC was also highly expressed in various cancer types, as shown in liver, prostate, and breast cancers 10 , 11 . Although many pieces of evidence supported the involvement of TMBIM6 in the development of various cancers, the molecular mechanism underlying the role of TMBIM6 in cancer progression has been less studied.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, we reported that Sp1 and PKC regulate the transcriptional expression of TMBIM6 8 . PKC was also highly expressed in various cancer types, as shown in liver, prostate, and breast cancers 10 , 11 . Although many pieces of evidence supported the involvement of TMBIM6 in the development of various cancers, the molecular mechanism underlying the role of TMBIM6 in cancer progression has been less studied.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, PKCδ has been shown to function as a tumor promoter in most (but not all) mouse models of cancer studied (Mauro et al, 2010; Symonds et al, 2011; Allen-Petersen, Carter, Ohm, & Reyland, 2014). Changes in PKCδ expression have been reported in some human tumors (Kahl-Rainer, Karner-Hanusch, Weiss, & Marian, 1994; D’Costa et al, 2006; Reno et al, 2008; Fukase et al, 2011) and increased PKCδ expression correlates with poor prognosis in specific subtypes of human breast cancer (McKiernan et al, 2008; Allen-Petersen et al, 2014). Notably, functional genomic alterations of PKCδ are rarely found (Antal & Newton, 2014).…”
Section: Biological Functions Of Pkcδmentioning
confidence: 99%
“…Similarly, Mischak et al showed that overexpression of PKCδ could suppress proliferation of NIH 3T3 cells (Mischak et al, 1993), and similar findings have been reported in a variety of cancer cells. For instance, PKCδ negatively regulates the Wnt pathway to suppress proliferation of colon cancer cells (Hernández-Maqueda, Luna-Ulloa, Santoyo-Ramos, Castañeda-Patlán, & Robles-Flores, 2013), Gli1 activation and Hedgehog signaling in hepatocellular carcinoma(Cai, Li, Gao, Xie, & Evers, 2009), ERK activation in breast cancer cells, and the proliferation and migration of human malignant fibrous histocytoma cells (Fukase et al, 2011). PKCδ also regulates apoptosis in prostate cancer cells through a mechanismin dependent of caspase cleavage and that involves the p38MAPK pathway (Fujii et al, 2000; Tanaka, Gavrielides, Mitsuuchi, Fujii, & Kazanietz, 2003).…”
Section: Biological Functions Of Pkcδmentioning
confidence: 99%
“…This is exemplified by the use of prostate cancer cells as a model system to study distinct roles of PKC isozymes in apoptosis in prostate cancer cells [25], in which treatment of LNCaP, but not DU 145 and PC-3 cells, with PMA induces apoptosis [26]. Consistent with their differential roles in cell-based studies, the expression level of several PKC isozymes in some human cancers inversely correlates with the aggressiveness of the disease [27, 28]. However, the mechanism by which down-regulation of PKC isozymes regulates cancer cell growth remains unknown.…”
Section: Introductionmentioning
confidence: 99%